The Evaluasi Kinerja Model Page Pada Pengeringan Lapisan Tipis Umbi Iles-Iles - Mukmin Mukmin; Junaedi Muhidong; Abdul Azis (Jurnal Agritechno, 2021)
The iles-iles is an umber plant having a high economic potential. This plant can only grow in tropical and subtropical areas. This study aims to evaluating the accuracy of the page model in estimating the moisture ratio of the iles-iles in the form of slice during the thin layer drying process. This research uses 450C and 550C drying temperature as well as the thickness of iles-iles 1,0 cm and 0,5 cm. Drying air velocity was used at 1,0 m/s. The observation parameters used on this study were the weight of the sample and the drying time. Results of this study are the water-level drop pattern, moisture ratio drop pattern, the value of page model drying, and page model evaluations. Those results describe that the relation between the predictive value and the observation value of moisture ratio create regression equations without the intersept with R2 approaching value. Consequently, the acquired page model is preferred to give partial predictions of iles-iles. Meanwhile the R2 value is 0.998, the chi-squared, value is 5.202x102, and the RMSE value is. The concise of R2, Chi-Squared, and RMSE with the previous research had relatively small value that indicated that a page model drying performance on the study was also quite good